Eksplorasi Penggunaan Media Pembelajaran Big Book Dalam Mengenalkan Alat-Alat Optik Kepada Peserta Didik - Natasya; Wiwik Kurniyati; Femi Br Ginting; Afifa Suci Nahara; Oliver Chelsea Sitanggang; Desy Rosmalinda (Universitas Muhammadiyah Kuningan, 2025)
This research aims to explore the use of Big Book learning media in introducing optical tools to elementary school students. This study uses a qualitative approach with the type of library research. These sources are systematically analyzed to select, explore, evaluate, and synthesize the latest findings. The literature search is estimated to be published from 2020 to 2024. The source of the article searched or selected through an online search with the Google Scholar database uses the keywords